Impact of Schedule Uncertainty on Freight Train Services at PT. KAI - Zulfan Nur, Muhammad; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Transportation by land, sea, and air is one of the extensive ways to ship goods. Trains are one of the popular ways of land transportation. Goods sent by train are included in the category of retail or containers. Jakarta Gudang Station Gudang handles the delivery of Parcel Ons, and there are ten dispatchers who have signed contracts for this service. A series of goods are sent through the train fleet by the Freight Transportation division of PT. Indonesian Railways (Persero). Customers will not use our services again if they are not satisfied. We are confident that our customers are not satisfied with a particular problem. One way to find out if customers are satisfied with the service is to fill out a survey. The study aims to determine how effective rail transportation services are in transporting business-to-business (B2B) and customer-to-business (B2C) goods. The goal is to ensure that the goods reach their intended destination. . Observations, interviews, and analysis of documents are used to collect data. To compare the volume of cargo transported by two types of business services, the ANOVA test is used. Freight transportation services by rail are divided into container freight transportation and retail freight transportation (small package ounces). Jakarta Gudang Station carries out package delivery and collaborates with 10 expeditions. PT KAI (Persero) provides railways for the transportation of goods and, has found that the services provided have an impact on customer satisfaction. Service failures can lead to customer dissatisfaction, which can be measured using surveys. So far, customers are happy with the service provided. Due to the very limited capacity of highways in some countries, such as Trans Java traffic, certain routes require capacity building and the construction of new lines gradually.